Psychological factors associated with medication noncompliance in schizophrenic patients who attending psychiatric teaching hospitals - Ashoor, Fatin Ghani; Mohammed , Saja Hashim (International Journal of Psychosocial Rehabilitation, 2020)
A descriptive cross-sectional study that was carried out during the period of March 20, 2019 to September 10, 2019. The study aim was to assess the level of medication non- compliance and the psychological factors associated with medication non- compliance among schizophrenic patients. A purposive (Non-Probability) sample of 150 schizophrenic outpatients was selected. Data were collected through the use of the constructed questionnaire and the process of the structured interview and administrative questionnaire as means for data collection The questionnaire was constructed as a main instrument, which consisted of three parts; the first part includes two sections which are the covering letter to obtain the agreement of patients to participate in the present study and the socio- demographic and clinical characteristics of the patients; the second part is the questionnaire with 34 items measure the psychosocial factors associated with medication non- compliance in schizophrenic patients; the third part of Questionnaire is concerned with medication non- compliance level in patients with schizophrenia. The study result found that psychological factors were highly associated with non-compliance to medication among patients (77.3%). The findings also show that high level of non-compliant to medication (60.7%). The study recommended Put in place psycho education programmers for individual patients, relatives and the community, to demystify mental illness. This includes provision of trained personnel and material resources to facilitate this.